(untitled) (International journal of medical sciences, 2026)
Sepsis remains a leading cause of morbidity and mortality among surgical patients worldwide. It is defined as life-threatening organ dysfunction caused by a dysregulated host response to infection. Surgical patients are particularly vulnerable due to invasive procedures, trauma, postoperative complications, and immunosuppression. Early diagnosis, prompt antimicrobial therapy, adequate fluid resuscitation, and timely source control are critical determinants of survival. Delays in intervention significantly increase mortality. Advances in critical care medicine, including early goal-directed therapy, sepsis bundles, and improved organ support strategies, have improved outcomes. This article reviews the pathophysiology of sepsis in surgical patients, diagnostic criteria, importance of early source control, and modern evidence-based management strategies.